Recent trends in revision knee arthroplasty in Germany - Markus Rupp (Nature Portfolio, 2021)
Abstract We aimed to answer the following questions: (1) How did numbers of revision knee arthroplasty procedures develop in Germany over the last decade compared to primary TKA? (2) How high was the percentage of septic interventions in knee prosthesis revisions? (3) Which treatment strategy was chosen for surgical treatment of knee PJI? Revision arthroplasty rates as a function of age, gender, infection and type of prosthesis were quantified based on Operation and Procedure Classification System codes using revision knee arthroplasty data from 2008 to 2018, provided by the Federal Statistical Office of Germany (Destatis). In 2018, a total number 23,812 revision knee arthroplasties were performed in Germany, yielding an overall increase of 20.76% between 2008 and 2018. In comparison, primary TKA procedures increased by 23.8% from 152,551 performed procedures in 2008 to 188,866 procedures in 2018. Hence, 12.6% of knee arthroplasties required a revision in 2018. Septic interventions increased by 51.7% for all revisions. A trend towards higher numbers in younger patients was observed. Compared to 2008, 17.41% less DAIR procedures were performed, whereby single-stage and two- or multi-stage change increased by 38.76% and 42.76% in 2018, respectively. The increasing number of revision knee arthroplasty in Germany, especially in younger patients and due to infection, underlines the need for future efforts to improve treatment strategies to delay primary arthroplasty and avoid periprosthetic joint infection.